Experimental Sleep Restriction Causes Endothelial Dysfunction in Healthy Humans. Issue 6 (25th November 2014) - Calvin, Andrew D.; Covassin, Naima; Kremers, Walter K.; Adachi, Taro; Macedo, Paula; Albuquerque, Felipe N.; Bukartyk, Jan; Davison, Diane E.; Levine, James A.; Singh, Prachi; Wang, Shihan; Somers, Virend K.
Abstract : Background: Epidemiologic evidence suggests a link between short sleep duration and cardiovascular risk, although the nature of any relationship and mechanisms remain unclear. Short sleep duration has also been linked to an increase in cardiovascular events. Endothelial dysfunction has itself been implicated as a mediator of heightened cardiovascular risk. We sought to determine the effect of 8 days/8 nights of partial sleep restriction on endothelial function in healthy humans. Methods and Results: Sixteen healthy volunteers underwent a randomized study of usual sleep versus sleep restriction of two‐thirds normal sleep time for 8 days/8 nights in a hospital‐based clinical research unit. The main outcome was endothelial function measured by flow‐mediated brachial artery vasodilatation (FMD). Those randomized to sleep restriction slept 5.1 hours/night during the experimental period compared with 6.9 hours/night in the control group. Sleep restriction was associated with significant impairment in FMD (8.6±4.6% during the initial pre‐randomization acclimation phase versus 5.2±3.4% during the randomized experimental phase, P =0.01) whereas no change was seen in the control group (5.0±3.0 during the acclimation phase versus 6.73±2.9% during the experimental phase, P =0.10) for a between‐groups difference of −4.40% (95% CI −7.00 to −1.81%, P =0.003). No change was seen in non‐flow mediated vasodilatation (NFMD) in either group. Conclusion: In healthy individuals, moderate sleep restriction causes endothelial dysfunction. Clinical Trial Registration: URL: ClinicalTrials.gov. Unique identifier: NCT01334788.